2012
DOI: 10.1155/2012/972679
|View full text |Cite
|
Sign up to set email alerts
|

Vasoprotection by Dietary Supplements and Exercise: Role of TNFαSignaling

Abstract: Vascular dysfunction contributes to the pathogenesis of various cardiovascular diseases. Dietary supplements, including fish oil, dietary fibers, and various natural products, and exercise training exert vasoprotective effects. However, the mechanisms underlying the vasoprotective benefits of dietary supplements and physical activity demand extensive investigation. Accumulating evidence suggests that inflammatory cytokine tumor necrosis factor-alpha (TNFα) plays a pivotal role in the dysregulation of macrovasc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 55 publications
(54 reference statements)
0
18
0
Order By: Relevance
“…Several preventive and therapeutic options have been proposed to counteract these biochemical alterations, including, among others, dietary supplementation resulting in antioxidant effects, antioxidant vitamins, and administration of NSAIDs at low doses [2629]. It has also recently been shown that a healthy diet and regular moderate physical exercise have antioxidant and anti-inflammatory effects, reducing the risk of chronic diseases or contributing to its treatment [30–32].…”
Section: Discussionmentioning
confidence: 99%
“…Several preventive and therapeutic options have been proposed to counteract these biochemical alterations, including, among others, dietary supplementation resulting in antioxidant effects, antioxidant vitamins, and administration of NSAIDs at low doses [2629]. It has also recently been shown that a healthy diet and regular moderate physical exercise have antioxidant and anti-inflammatory effects, reducing the risk of chronic diseases or contributing to its treatment [30–32].…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence suggests that TNF-a induces vascular inflammation, monocyte adhesion to endothelial cells, vascular oxidative stress, apoptosis, and atherogenic response and participates in the regulation of thrombosis and coagulation through NFjB, Sp1, JNK, p38, and STAT3 pathways. 33 Dietary supplements and exercise training decrease TNF-a production and ameliorate TNF-a-mediated pathological changes in vasculature. Thus, the inhibitory effects of dietary supplements, including fish oil, dietary fibers, and various natural products, as well as physical exercise on TNF-a production and TNF-a signaling may contribute to their vasoprotective properties.…”
Section: Discussionmentioning
confidence: 99%
“…Quercetin exerts multiple biological effects -antioxidant, hypoglycemic, neuroprotective and anti-inflammatory -in T1DM (3,(10)(11)(12)(13)(14)(15)(16)(17). Recent research has demonstrated the beneficial effects of exercise training on preventing diabetic vascular compli-cations by reducing oxidative/nitrosative stress and inflammation (3,14,(18)(19)(20)(21)(22). Therefore, in the current study we evaluated the effects of combining quercetin treatment with moderate exercise training in preventing carotid artery injuries in diabetic rats through a reduction of glycemia and oxidative stress.…”
Section: Introductionmentioning
confidence: 99%